Between Loyalty and Integrity: The Paradox of Organizational Support and Employee Behavior in Healthcare - Anna Kridaningsih; Ratna Agustina; Eny Nuraeni (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This research investigates the interplay between Perceived Organizational Support (POS), Organizational Identification (OI), Unethical Pro-Organizational Behavior (UPB), and Organizational Citizenship Behavior (OCB) among healthcare professionals at RSU Dr. Iskak, Tulungagung. Employing a quantitative methodology with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0, data from 150 employees were analyzed to determine the direct and indirect effects of POS on workplace behaviors. The results indicate that POS significantly affects both UPB and OCB, with OI serving as a key mediating factor. Employees with a strong perception of organizational support tend to develop a heightened sense of identification with their organization, which in turn promotes discretionary behaviors, both constructive and ethically questionable. The study highlights that OI positively influences UPB, suggesting that employees with deep organizational attachment may justify unethical actions in pursuit of organizational objectives. Simultaneously, the positive indirect impact of OI on OCB affirms that a strong identification with the organization encourages voluntary prosocial behaviors. These findings emphasize the dual effects of organizational identification, reinforcing the necessity for organizations to cultivate employee commitment while instilling ethical leadership and well-defined behavioral standards. The practical implications suggest that healthcare institutions must establish clear ethical guidelines and reinforce leadership practices that support ethical conduct while fostering organizational loyalty.